Pengelolaan Akun Instagram @kominfopadangpanjang Sebagai Bentuk Kegiatan Online Public Relations - Ghievanny, Ezga Mayzamelilla; Risdayah, Enok; Astuti, Dyah Rahmi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to find out how the steps taken by Diskominfo Padang Panjang in managing the @kominfopadangpanjang Instagram account. This study uses a qualitative approach, with a descriptive method. The results obtained are the management of the @kominfopadangpanjang instagram account, has four stages, namely: 1) sharing, participating in using social media to connect with the community and building public trust, 2) optimizing, optimizing information by producing various types of information content, and visual enhancement of content, 3) Manage, conduct media monitoring and quick response, and 4) Engage, involving the community as part of communication planning through Instagram @kominfopadangpanjang.